The Scandinavian Conference on Middle East Studies: 24 -27 Rabi al Akhir 1413 / 22-25 October 1992 Copenhagen University, Copenhagen, Denmark (American Journal of Islam and Society, 1993)
The Nordic Association of Middle East Studies, which was establishedin 1989 in Uppsala, Sweden, recently held its second conference.Delegates from Denmark, Sweden, Norway, and Finland participated.John O. Voll (who has with Swedish ancestors), chairman of the MiddleEast Studies Association (MESA), came as guest lecturer.The conference's leitmotif was "Diversity and Unity of the MiddleEastern World," which was also the theme of Voll's lecture. By reconceptualizingthe understanding of Middle East as a holistic region, one inwhich sociopolitical, economic, and cultural patterns have been regardedwithin a narrow "Muslim" or "Islamic," framework, he objected to standardizedconcepts and generalizations. He used the case of the Egyptianpeasant-how new developments and changed structures have transformedthe peasant of the 1970s into the different peasant of the 1990s.He also argued that concepts themselves can be actors in history whenthey have been conceptualized. Thus they do not always describe reality ...